The Impact of Local Economic Growth Target Setting on the Quality of Public Occupational Health: Evidence From Provincial and City Government Work Reports in China - Wang, Fan-Fan; Deng, Wen-Jing; Cheng, Hao; Gao, Qing; Deng, Zi-Wei; Deng, Han-Cong (Frontiers in Public Health, 2021)
To coordinate safety and development is a key issue for Chinese government to consider in advancing the modernization of the national governance system and governance capacity. Based on the data from the government work reports of 31 provinces (autonomous regions and municipalities) of China and 21 cities in Guangdong Province of China from 2001 to 2019, this paper examines the impact of local economic growth target setting on the quality of public occupational health from two perspectives, the first is economic growth target constraint and the second is economic growth target gap between countries and provinces or between provinces and cities. The results show that economic growth target constraint and gap have a significant impact on the quality of public occupational health, and a "U-shaped" trend is presented at both provincial level and city level, which firstly promotes and then inhibits. Those conclusions are still valid after the method of instrumental variables, generalized method of moments and other robustness tests. This paper for the first time shows the impact of economic growth management by objectives in the field of occupational health and provides useful inspiration for further optimizing government management by objectives, improving the quality of public occupational health and realizing high-quality economic development.